THE KINETIC PROFILE OF IRON DISSOLUTION FROM LATERITE ORE IN CHLORIC ACID SOLUTION - Solihin Solihin; Pratama Arinaldo; Nanda Sari Dewi; Haryadi Permana (Puslitbang tekMIRA, 2019)
Indonesia has large amount of laterite deposits located in Southeast Sulawesi. The laterite contains significant amount of iron. The ore has been processed through high temperature. The high temperature consumes a lot of energy and releases a lot of carbon dioxide. The low temperature of the process is simple and needs less energy. Leaching the ore is the important stage in low temperature which determines the recovery of valuable metal from the ore. This work observes the kinetic aspect of iron dissolution in the process based on the shrinking core model. The data of iron dissolution at temperature 30, 50, 70 and 90°C are plotted into chemical reaction control and diffusion control equations. The result shows that at 30 and 50°C, the whole leaching process is controlled by the rate balance between chemical reaction and diffusion, whereas at 70 and 90 °C, the reaction is controlled by diffusion.